A tale of two rivers: development, destruction, and despair in Ongata Rongai, Kenya - Howland, Olivia (Frontiers Media, 2023)
Introduction: Ongata Rongai is a rapidly growing peri-urban space in Nairobi Metropolitan, Kenya. The last 10 years have seen exponential population growth and building development leading to overcrowding and pressure on water and environmental resources. This original research sheds light on interactions among humans, animals, and this rapidly changing urban environment. It is therefore a quintessentially One Health study.